Sequencing and analysis of the complete mitochondrial genome of Hyla suweonensis (Anura: Hylidae) - Mu-Yeong Lee; Hey Sook Jeon; Mi-Sook Min; Junghwa An (Mitochondrial DNA. Part B. Resources, 2017)
The present study reports the complete mitochondrial genome of the Suwon tree frog Hyla suweonensis from South Korea. This endangered species is endemic to Korea. The circular mitogenome of H. suweonensis includes 16,895 bp length and contains 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and a non-coding region, which is the typical gene arrangement found in the available Hylinae mitogenomes. Phylogenetic analysis of six Hyla spp. mitochondrial genomes revealed that H. suweonensis is closer to H. tsinlingensis.